English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-08 03:17:30 · 11 answers · asked by Deepak B 1 in Science & Mathematics Mathematics

11 answers

(a+b)^2=(a+b)*(a+b)=
=a^2+ab+ab+b^2=
a^2+2ab+b^2
...

2007-09-08 03:22:26 · answer #1 · answered by Anonymous · 0 0

(a + b) (a + b)
= a ² + a b + b a + b ²
= a ² + a b + a b + b ²
= a ² + 2 a b + b ²

2007-09-09 22:38:56 · answer #2 · answered by Como 7 · 0 0

dude let us assume the value of a=2,b=3.

now, (a+b)^2=(2+3)^2

= 5^2

=25.

now lets check a^2+b^2+2ab

2^2+3^2+2*3*2

=4+9+12

=25.

therefore from the two answers

(a+b)^2=a^2+b^2+2ab.

2007-09-08 03:24:15 · answer #3 · answered by nawaz_xan6 2 · 0 0

(a+b)^2. Expand out the brackets using FOIL.

(a+b)^2 = a^2 + ab + ba + b^2.
= a^2 + 2ab + b^2
= a^2 + b^2 = 2ab as required.

2007-09-08 03:22:29 · answer #4 · answered by steppy333 2 · 0 0

I think you mean squared when you're typing this, just so you know, (a+b)^2 is squared. To figure this out you just have to expand (a+b)^2:

(a+b)^2 *expand the exponent
= (a+b) x (a+b) *multiply everything in one bracket by everything in the other
= (axa) + (axb) + (axb) + (bxb) *simplify the brackets
= a^2 + ab + ab + b^2 *now collect like-terms
= a^2 + 2ab + b^2

You could also use the Pascal's Triangle method, go look it up if you want, but it's kind of annoying to work with.

2007-09-08 03:27:29 · answer #5 · answered by Anonymous · 0 0

(a+b)^2=(a+b)(a+b)
=a(a+b)+b(a+b)
a^2+ab+ab+b^2
=a^2+b^2+2ab. ANS.

2007-09-08 03:41:50 · answer #6 · answered by Anonymous · 1 0

i think you mean (a+b)^2 = a^2 + 2ab + b^2

but here's how...

(a+b)^2 = (a+b)*(a+b)

multiply that out and you get

a*a + a*b + b*a + b*b

simplify a little and you get

a^2 + ab + ab + b^2

simplify some more and you get

a^2 + 2ab + b^2

see? :)

2007-09-08 03:25:26 · answer #7 · answered by Andy 1 · 0 0

(a+b)2 means that it's a+b plus another a+b so that's (a+b)x(a+b) so it's a x a+b and b x a+b so that's axa plus axb plus bxa plus bxa (axa+axb+bxa+bxb) or a^2 + ab +ab + b^2 or a^2 + 2ab + b^2 then switch the 2nd with the 3rd.

2007-09-08 03:41:45 · answer #8 · answered by Josh Kortos duh! 2 · 0 0

Simple. 1) Take a square with side 'a' (say 8cm). 2)Take another square with side b, say 6 cm 3) Take 2 rectangles, each with length 'a' i.e. 8cm and breadth 'b' i.e. 6cm. 4)Take a fourth square with side a+b i.e. 14 cm. Now paste the first two squares and the two rectangles on the last square. You will see that they overlap it completely. This proves the identity.

2016-04-03 10:48:33 · answer #9 · answered by Anonymous · 0 0

a^2 +ab+ab+b^2
then
a^2+2ab+b^2....
You can also use binomial theorem

2007-09-08 03:26:43 · answer #10 · answered by wisten 2 · 0 0

fedest.com, questions and answers